أثر الرضا الوظيفي في تعزيز الانغماس الوظيفي لدى أعضاء هيئة التدريس بالجامعة الجزائرية - عبد الرحمان, ياسر; بوغرزة, رضا; حديد, يوسف (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى محاولة التعرف على أثر الرضا الوظيفي بمختلف أبعاده (محتوى العمل، ظروف العمل، نظام الأجور الترقيات، العلاقة بين زملاء العمل، نمط الإشراف) في تعزيز الانغماس الوظيفي لدى أعضاء هيئة التدريس بالجامعة الجزائرية. ومن أجل تحقيق هذا الهدف تم الاعتماد على استبيان من إعداد الباحثين كأداة رئيسية لجمع البيانات اللازمة من أفراد عينة الدراسة والتي بلغ حجمها 420 أستاذا دائما من مختلف جامعات الوطن، حيث تم توزيع الاستبيانات عن طريق البريد الإلكتروني، وتم معالجة البيانات المجمعة إحصائيا باستحدام برنامج (SPSS). أظهرت نتائج الدراسة أنه يوجد أثر للرضا الوظيفي في تعزيز الانغماس الوظيفي لدى أعضاء هيئة التدريس بالجامعة الجزائرية، أما بالنسبة لأبعاد الرضا الوظفي فقد تأكد وجود أثر لكل من بعد محتوى العمل، بعد نظام الأجور الترقيات، وبعد العلاقة بين زملاء العمل في تعزيز الانغماس الوظيفي لدى أعضاء هيئة التدريس. وعلى ضوء النتائج المتوصل إليها تم تقديم جملة من التوصيات. This study aims at trying to identify the impact of job satisfaction in its various dimensions (work content, working conditions, wage system, promotions, relationship between co-workers, and supervision pattern) in enhancing job involvement among faculty members at the Algerian University. In order to achieve this goal, the researchers relied on a questionnaire as a main tool to collect the necessary data from the members of the study sample, whose size reached 420 permanent professors from various universities in the country. The questionnaire was distributed via e-mail, and the data collected were statistically processed using the (SPSS) program. The results of the study showed that there is an impact of job satisfaction on enhancing job involvement among faculty members at the Algerian University. As for the dimensions of job satisfaction, it was confirmed that there is an impact of the dimensions of work content, the wage system, promotions, and the relationship between co-workers in enhancing the career immersion of faculty members. In light of the findings, a number of recommendations were presented.
The Effect of Job Satisfaction in Enhancing Job Involvement among Faculty Members in Algerian Universities
مقال
Keywords: الرضا الوظيفي ، محتوى العمل، نمظ الإشراف، الانغماس الوظيفي، عضو هيئة التدريس، الجامعة; Job Satisfaction; Work content; Moderate supervision; Job Involvement; Faculty member; The University.